The Change of Systemic Immune-Inflammation Index Independently Predicts Survival of Colorectal Cancer Patients after Curative Resection - Qingqing Chen; Haohao Wu; Xinwei Guo; Ke Gu; Wenjie Wang; Xiaochen Chen; Shengjun Ji; Hui Yang; Jiahao Zhu (Mediators of Inflammation)
Background. The systemic immune-inflammation index (SII) has an important role in predicting survival in some solid tumors. However, little information is available concerning the change of the SII (∆SII) in colorectal cancer (CRC) after curative resection. This study was designed to evaluate the role of ∆SII in CRC patients who received surgery. Methods. A total 206 patients were enrolled in this study. Clinicopathologic characteristics and survival were assessed. The relationships between overall survival (OS), disease-free survival (DFS), and ∆SII were analyzed with both univariate Kaplan-Meier and multivariate Cox regression methods. Results. Based on the patient data, the receiver operating characteristic (ROC) optimal cutoff value of ∆SII was 127.7 for OS prediction. The 3-year and 5-year OS rates, respectively, were 60.4% and 36.7% in the high-∆SII group (>127.7) and 87.6% and 79.8% in the low-∆SII group (≤127.7). The 3-year and 5-year DFS rates, respectively, were 54.1% and 34.1% in the high-∆SII group and 80.3% and 78.5% in the low-∆SII group. In the univariate analysis, smoking, pathological stages III-IV, high-middle degree of differentiation, lymphatic invasion, vascular invasion, and the high-ΔSII group were associated with poor OS. Adjuvant therapy, pathological stages III-IV, vascular invasion, and ΔSII were able to predict DFS. Multivariate analysis revealed that pathological stages III-IV (HR=0.442, 95% CI=0.236-0.827, p=0.011), vascular invasion (HR=2.182, 95% CI=1.243-3.829, p=0.007), and the high-ΔSII group (HR=4.301, 95% CI=2.517-7.350, p<0.001) were independent predictors for OS. Adjuvant therapy (HR=0.415, 95% CI=0.250-0.687, p=0.001), vascular invasion (HR=3.305, 95% CI=1.944-5.620, p<0.001), and the high-ΔSII group (HR=4.924, 95% CI=2.992-8.102, p<0.001) were significant prognostic factors for DFS. Conclusions. The present study demonstrated that ∆SII was associated with the clinical outcome in CRC patients undergoing curative resection, supporting the role of ∆SII as a prognostic biomarker.